Impact of temperatures on Hessian fly (Diptera: Cecidomyiidae) resistance in selected wheat cultivars (Poales: Poaceae) in the Great Plains region - Chen, Ming-Shun; Wheeler, Shanda; Wang, Haiyan; Whitworth, R. Jeffery (My University, 2014)
Changes in temperature can result in fundamental changes in plant physiology. This study investigated the impact of different temperatures from 14 to 26°C on the resistance or susceptibility to the Hessian fly, Mayetiola destructor (Say), of selected wheat cultivars that are either currently popular in the Great Plains area or soon to be released to this region. We found that many wheat cultivars including ‘Bill Brown,’ ‘Byrd,’ ‘Endurance,’ ‘Fuller,’ ‘GA-031257-10LE34,’ and ‘KS09H19-2-3’ were susceptible to Hessian fly infestation at ≥20°C, but became resistant at a certain lower temperature, depending on different cultivars. These cultivars were classified as Hessian fly susceptible according to the traditional standards, and their impact on Hessian fly management needs to be reevaluated. However, many wheat cultivars that were resistant at ≤20°C became destabilized at a certain higher temperature. Phenotypic variations among the resistant cultivars at different temperatures were also observed, suggesting potential different resistance mechanisms. Studies on the genetic and molecular mechanisms associated with resistance at different temperatures are needed, which may lead to improved wheat cultivars with more durable resistance to Hessian fly infestation.
Citation: Chen, Ming-Shun, Shanda Wheeler, Haiyan Wang, and R. Jeffrey Whitworth. 2014. “Impact of Temperatures on Hessian Fly (Diptera: Cecidomyiidae) Resistance in Selected Wheat Cultivars (Poales: Poaceae) in the Great Plains Region.” Journal of Economic Entomology 107 (3): 1266–73. https://doi.org/10.1603/EC13357.
Keywords: Hessian fly; Mayetiola destructor; Plant resistance; Temperature effect; Wheat